Consolidation of university social responsibility policies for sustainable development: An approximate analysis in the management of the Venezuelan Public University (Ágora de Heterodoxias, 2022)
It was performed a review of documents and articles including theoretical constructs that would allow understanding the process of implementation and the route to consolidation of University Social Responsibility (RSU) politics in Venezuelan universities. These institutions are going thru a crisis unable to implement RSU politics. It is essential the effort and commitment of those who lead their destinies, their community (including graduates) and the Venezuelan State, jointly, to be able to maintain academic quality and to form citizens committed to world issues, with skills to move forward to reach the goals of Sustainable Development Objectives (ODS), without leaving out RSU. To reach out the goals of ODS in the country and achieve a more sustainable environment for everyone, it is essential the self-diagnosis and the adoption of an integral approach of the RSU, considering all ambits of university action, with training, research and social projection of the university socially responsible.
Keywords: resource conservation; universities; education quality